PEMAHAMAN KONSEP SISWA MELALUI SKEMA BLENDED LEARNING MENGGUNAKAN LEMBAR KERJA BERBASIS SIMULASI - Ogi Danika Pranata; Seprianto Seprianto (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2023)
Learning, especially in physics, could be done in a combination of face-to-face and online. However, the scheme of this combination is unclear. Both type of learning need to be synchronized so that learning becomes effective. The solution is to involve technology in the learning process. Technology can be used as a learning medium and assessment. Blended learning scheme using worksheet based on PhET (Physics Education Technology) simulation was applied in Basic Physics course. This solution is expected to create link between face-to-face and online learning. Mixed methods with embedded design was applied. The population is quite small, namely 32 students so that all population is applied as a sample. Data on students' conceptual understanding were collected using a test. Class discussions became the basis for qualitative data which was further explored through interviews. Conceptual understanding was found in the high category for vector and projectile motion when taught through a blended learning scheme using student worksheets. The averages scores for vector in 1 dimension and 2 dimensions are 85.94 and 77.93, respectively. Then the average scores for the projectile motion is 80.93. Furthermore, through discussions and interviews, various misconceptions and their causes.